2020
DOI: 10.3390/ijerph17124240
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Social Support of People on Peritoneal Dialysis: Mixed Methods Research

Abstract: Although some study has been made into quality of life in patients with peritoneal dialysis, little is known about how this relates to social support. The aim of this paper was to study health-related quality of life, perceived social support and the experiences of people receiving peritoneal dialysis. A cross-sectional study was conducted using quantitative and qualitative methodologies, between June 2015 and March 2017. Fifty-five patients receiving peritoneal dialysis were studied. The most affected quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 67 publications
2
10
0
6
Order By: Relevance
“…Moreover, QoL was positively correlated with social support. The present analysis corresponds with the studies by Dębska et al and Sitjar-Suñer et al, who demonstrated that social support is a key factor for perceived quality of life [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, QoL was positively correlated with social support. The present analysis corresponds with the studies by Dębska et al and Sitjar-Suñer et al, who demonstrated that social support is a key factor for perceived quality of life [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, QoL was positively in uenced by the perceived available emotional and actually received support in both study groups, while in the case of respondents who had miscarried, this was also true for perceived available instrumental support. The present analysis corresponds with the studies by Dębska et al and Sitjar-Suñer et al, who demonstrated that social support is a key factor for perceived quality of life [20,21].…”
supporting
confidence: 92%
“…Between the dialysate replacements, the dialysate stays in the body and enables detoxication. As the treatment can be arranged flexibly in terms of time and place, PD can enable a more autonomous life [1]. Both dialysis treatments are symptomatic but life-sustaining.…”
Section: Introductionmentioning
confidence: 99%